Timeshare. Prawo periodycznego świadczenia wypoczynkowego – geneza i przedmiot prawa - Akińcza, Jerzy (Kortowski Przegląd Prawniczy, 2022)
The right to periodic holiday benefits, normatively referred to as timeshare, still remains a legal construction requiring legal analysis, which concerns, for instance, bringing It is important for the right of periodical recreation benefit to be defined incorrectly both doctrinally and normatively, what additionally justifies the consolidation of correct definition of the right of periodical recreation benefit, what concerns placing the right of periodical recreation benefit in the area of obligation.